2019
DOI: 10.31742/ijgpb.79s.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tagging of photoperiod responsive flowering in Indian bean [Lablab purpureus (L.) Sweet] Vinita Ramtekey*, Arpit Bhuriya, Dipendra Ayer, Vipulkumar Parekh, Kaushal Modha, Bhushan Kale, Gopal Vadodariya and Ritesh Patel (

Abstract: Photoperiod responsive flowering and growth habit might have played a key role in domestication of lablab bean (Lablab purpureus) and currently shifting its cultivation from intercropping to monoculture. Most of the landraces of lablab bean exhibit photoperiod sensitivity in flowering and indeterminate growth habit. A cross was made between GNIB21 and GP189 which are phenotypic extremes for photoperiod responsive flowering. The F1 hybrid exhibited dominant traits like indeterminate growth habit and photosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Two orthologs of pea TFL1a , GmTFL1a and GmTFL1b , were isolated from the soybean through molecular dissection; mapping analysis indicated that GmTFL1b was a candidate for Dt1 [ 45 ] . Cosegregation of the marker and TFL locus indicated that LprTFL is a homologue of the TFL1 in Indian bean [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two orthologs of pea TFL1a , GmTFL1a and GmTFL1b , were isolated from the soybean through molecular dissection; mapping analysis indicated that GmTFL1b was a candidate for Dt1 [ 45 ] . Cosegregation of the marker and TFL locus indicated that LprTFL is a homologue of the TFL1 in Indian bean [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A linkage relationship between growth habit and flowering homologues has been reported in soybean [ 52 , 53 ], pea [ 19 ] and common bean [ 2 ]. Linkage between growth habit and photoperiod-responsive flowering has been reported in Indian bean [ 5 , 6 ]. Two FT homologues GmFT2a and GmFT5a were found to be involved in the control of photoperiodic flowering in soybean [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations